The main context of the development of the agricultural economy in Szeklerland - Kelemen, Réka; Káposzta, József; Lőrinc, Balázs (Studia Mundi – Economica, 2023)
In the Szekler region of Romania, there is a strong tradition of agricultural activities, as agriculture still provides a livelihood for many people, but there are nevertheless a number of specific sectoral problems in the region. These difficulties include the fact that the land tenure structure has been significantly fragmented over the past decades, that a significant proportion of local youth have a high propensity to emigrate internationally, and that the entrepreneurial and alternative production skills of farmers with lower education levels are on average low. These data provide a good overview of the factors that most characterise the agricultural sector and farming society in Szeklerland, such as the problem of generational change and the lack of targeted policy measures to promote technological development. Based on these findings, the study presents the potential directions for the development of agricultural production in Szeklerland, in particular through the national polarity of agricultural enterprises and agricultural employment, the expansion of income from agricultural production and the activities of young farmers. Through this research, we will explore spatial-economic linkages that may determine the foundations of local futures and strategies for thriving locally.
Keywords: Szeklerland; agricultural economy; regional differences; economic development op-portunities